Effects of maternal nutrition regimen of ewes on performance, carcass, and meat traits of their feedlot-finished lambs - de ANDRADE, Nomaiaci [UNESP]; Sobrinho, Américo g. Da silva [UNESP]; Borghi, Thiago Henrique [UNESP]; Valença, Roberta de lima; Romanzini, Eliéder P. [UNESP]; VAN CLEEF, Eric H. C. B. (FapUNIFESP (SciELO), 2024)
The objective of this study was to evaluate the effects of diets with two energy levels fed to Ile de France ewes during the last third of gestation on the performance, carcass, and meat traits of their offspring. Treatments were: D0: maternal diet meeting the requirements for the last third of gestation, and D20: maternal diet containing an additional 20% energy requirements. Twenty single-born male lambs, ten from each group of ewes, were weaned at 60 d (18.3 ± 1.4 kg initial BW) and fed a common finishing diet. Animals were slaughtered when they reached 32 kg BW. Dry matter intake, average daily gain, feed conversion, and days on feed were unaffected by treatments (P≥0.09). No effects were observed on hot and cold carcass weights, dressing percentage, chilling loss, commercial cuts yields, and loin-eye area (P≥0.17). Meat pH, thawing loss, cooking loss, shear force, and water holding capacity were also not affected by treatments (P≥0.09). Temperature and meat color, as well as centesimal composition were similar between treatments (P≥0.27). Adding 20% energy on top of the requirements of Ile de France ewes during the last third of gestation does not influence the performance, carcass traits, nor meat traits of their offspring.
Keywords: energy; fetal programming; lamb; sheep; tissue composition